2008
DOI: 10.1021/ac702610a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Protein Stability and Ligand Binding Using a Chemical Modification- and Mass Spectrometry-Based Strategy

Abstract: Described here is a new technique, termed SPROX (stability of proteins from rates of oxidation), that can be used to measure the thermodynamic stability of proteins and protein-ligand complexes. SPROX utilizes hydrogen peroxide in the presence of increasing concentrations of a chemical denaturant to oxidize proteins. The extent of oxidation at a given oxidation time is determined as a function of the denaturant concentration using either electrospray or matrix-assisted laser desorption/ionization mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
201
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(220 citation statements)
references
References 41 publications
3
201
0
1
Order By: Relevance
“…Indeed, the results in Fig. 3 are consistent with the destabilizing effects of methionine oxidation that we have previously measured in the CypA system (11). In general, SPROX data obtained on nonoxidized peptides are expected to provide the most accurate measure of a protein's wild-type stability.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Indeed, the results in Fig. 3 are consistent with the destabilizing effects of methionine oxidation that we have previously measured in the CypA system (11). In general, SPROX data obtained on nonoxidized peptides are expected to provide the most accurate measure of a protein's wild-type stability.…”
Section: Resultssupporting
confidence: 87%
“…Whereas we have previously shown that accurate ΔΔG f values for some protein systems can be determined by SPROX, even if the protein oxidation products are destabilized (11), it is clear that not all protein-folding and ligand-binding interactions will be free from perturbation. However, as described above SPROX data obtained on nonoxidized forms of methioninecontaining peptides are expected to be useful regardless of the perturbing effects of the oxidation reaction.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…[1][2][3] In these approaches, binding is detected by the ligand's ability to increase the thermodynamic stability of its protein partner. 4 By interacting preferentially with the folded conformation(s), the ligand shifts the equilibrium away from the unfolded state, which is measured in a denaturation experiment.…”
Section: Introductionmentioning
confidence: 99%